응집 한외여과 조합 공정에서 플럭스와 선속도가 막오염에 미치는 영향에 관한 연구 - 문성용; 이상협; 김승현; 윤조희 (대한상하수도학회, 2005)
A coagulation/ultrafiltration membrane hybrid system was operated to treat river water with capacity of 0.06 m3/d. The impact on membrane fouling by flux and linear velocity was investigated. It is known that pressure increase is proportional to flux increase. However, pressure increase was much faster than theoretical value in the pilot plant test. So it was suggested that flux was important factor in ultrafiltration of continuous operation.Membrane fouling was decreased when linear velocity was increased. This phenomenon was found more obviously without coagulation. With the combination of coagulation and sedimentation, membrane fouling was not reduced conspicuously. Big particles formed during coagulation and sedimentation were destroyed by feed and circulation pumping, which resulted in little effect on membrane fouling reduction. The degree of destruction was similar at various linear velocities. In this study, the hollow fiber membrane was used and the system was operated in pressure type module. In case of the system used in this study, membrane fouling has been affected lightly by linear velocity variation when coagulation pretreatment was applied.